2023
DOI: 10.3390/biomedicines11051273
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Proteomic Analysis of Patients with Ascending Thoracic Aortic Aneurysm

Abstract: Background: There is a need for clinical markers to aid in the detection of individuals at risk of harboring an ascending thoracic aneurysm (ATAA) or developing one in the future. Objectives: To our knowledge, ATAA remains without a specific biomarker. This study aims to identify potential biomarkers for ATAA using targeted proteomic analysis. Methods: In this study, 52 patients were divided into three groups depending on their ascending aorta diameter: 4.0–4.5 cm (N = 23), 4.6–5.0 cm (N = 20), and >5.0 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Recent studies demonstrated the accumulation of CD4 + T cells, monocytes, macrophages, and B cells in the dilated arterial wall ( 3 , 4 ). In parallel, several cytokines including CCL5, HBD1, and ICAM1 were confirmed in association with AA ( 5 ). However, such endpoint-driven conclusions could only identify the potential of these targets as biomarkers, as it is challenging to characterize whether the appearance of these immune cells/inflammatory cytokines is a cause or a consequence of AA, which is one of the reasons why there is a lack of effective pharmacological interventions.…”
Section: Introductionmentioning
confidence: 92%
“…Recent studies demonstrated the accumulation of CD4 + T cells, monocytes, macrophages, and B cells in the dilated arterial wall ( 3 , 4 ). In parallel, several cytokines including CCL5, HBD1, and ICAM1 were confirmed in association with AA ( 5 ). However, such endpoint-driven conclusions could only identify the potential of these targets as biomarkers, as it is challenging to characterize whether the appearance of these immune cells/inflammatory cytokines is a cause or a consequence of AA, which is one of the reasons why there is a lack of effective pharmacological interventions.…”
Section: Introductionmentioning
confidence: 92%
“…Yang et al, demonstrated an increase in C18-ceramide in ATAAD, suggesting its role in aortic inflammation via association with NLRP3 in the NLR family [ 228 ]. Moreover, a novel comparison of a targeted proteomic approach has shown that patients with ATAA have increased serum levels of several inflammatory markers, such as IL-8, intracellular adhesion molecule-1 (ICAM1), C–C motif chemokine ligand 5 (CCL5), and human beta-defensin 1 (HBD1) (Table 3 ) [ 41 ].…”
Section: Sporadic and Genetic Biomarkers In Ataa(d)mentioning
confidence: 99%